Numerical study of an oscillating smaller cylinder in the wake of an upstream larger cylinder - Gao, Yangyang (2013)
A numerical study of flow around two tandem cylinders with unequal diameters was carried out. The upstream larger cylinder was fixed and the downstream smaller cylinder was allowed to oscillate in the transverse direction only. Comparisons of the experimental and numerical results were made to investigate the effects of the gap ratio on the maximum vibration amplitude and vortex shedding frequency. The results showed that the vibration response of the smaller cylinder was significantly affected by the presence of the upstream larger cylinder, and resulted in greatly reduced vibration amplitudes. With an increasing gap ratio, the vibration amplitude increased. However, the magnitude was lower than that corresponding to a single cylinder (with the same diameter as that of the downstream smaller cylinder) under the same flow conditions.